Optimization of plunger geometry and stroke settings on hydraulic performance of diaphragm metering pumps - Sonjaya, Muhammad Luthfi; Setyawan, Hendra; Ritonga, Jhordan; Sarifudin, Alfan; Nury, Dennis Farina (Jurnal Polimesin, 2025)
This study examines the influence of plunger diameter and stroke length on the performance of a hydraulic diaphragm metering pump, focusing on two key indicators: discharge pressure and flow rate. Experiments were conducted with five plunger diameters (7.90–9.00 mm) and three-stroke settings (100%, 75%, and 50%), validated in accordance with API 675 standards. Results show that each 1 mm increase in plunger diameter produced a consistent rise in flow rate across all stroke settings. Linear regression analysis revealed strong correlations, with flow rate increments of 67.54 mL/min per mm at 100% stroke, 60.78 mL/min per mm at 75% stroke, and 25.34 mL/min per mm at 50% stroke. High coefficients of determination (R²) confirm the robustness and predictive accuracy of these models. In addition to regression analysis, a two-way ANOVA was performed to statistically evaluate the effects of plunger diameter and stroke length, as well as their interaction, on pump performance. The ANOVA results confirmed that both parameters significantly affected flow rate (p 0.05), while discharge pressure was largely unaffected by stroke variation. The optimal configuration was achieved at a plunger diameter of 8.00 mm and 100% stroke, delivering performance that meets API 675 requirements. Importantly, this study proposes a novel validation framework for hydraulic diaphragm metering pumps based on API 675—a gap not fully addressed in prior research. These findings provide practical guidance for improving the efficiency and reliability of pump systems through optimized geometric and operational parameters.